The Optimizing Oral Communication Skills Through the Use of the RADEC Learning Model in Basic Natural Science Concepts Courses: Optimalisasi Keterampilan Komunikasi Lisan melalui Penerapan Model Pembelajaran RADEC pada Mata Kuliah Konsep Dasar IPA - Iyoh Maspiroh; Nur Rohmatillah; Nandang Kusmana; Yuliana Aristian (Fakultas Pendidikan Ilmu Keguruan, Universitas Pahlawan Tuanku Tambusai, 2026)
Abstract This research aims to determine the effect of using the RADEC learning model on the oral communication skills of elementary school teacher education students. Much research has been carried out regarding the RADEC learning model. However, most focus on learning outcomes and students' thinking abilities. So far, no research has been found regarding the influence of the RADEC learning model on students' oral communication skills and this research attempts to fill this gap. The research population consisted of 125 elementary school teacher education students. The research sample was taken by purposive sampling with a total of 25 students in the experimental class and 25 students in the control class. The research method used is quasi-experimental. The data was then analyzed using an independent t test to determine the significance of differences in students' communication skills in the control group and the treatment group. The results of this research show that there is an increase in the oral communication skills of elementary school teacher education students after using the RADEC learning model.